"The honored actress of RA Raisa Mkrtchyan" - Aghajanyan Աննա Ստեփանի (Musical Armenia, 2017)
The author represents performing pedagogical activity of the honored actress of RA, professor of YSC, the pop singer, pianist Raisa Mkrtchyan. After the termination of school, she since 1969 teaches in the beginning on piano department and then on the department of pop singing. To the 50th anniversary of college in connection with long-term fruitful pedagogical activity Raisa Mkrtchyan has been awarded with the Gold medal of the Prime minister of RA, and to anniversary with the Gold medal of the Ministry of Education and Science.